2021
DOI: 10.33256/hb156.1113
|View full text |Cite
|
Sign up to set email alerts
|

Cloacal anatomy and sex determination in Tiliqua sp.

Abstract: A rigid endoscope was used to examine the cloacae of an adult pair of Tiliqua gigas gigas, and single specimens of Tiliqua gigas evanescens and Tiliqua sp. (Irian Jaya form). Throughout the procedure the animals showed no signs of stress. Clear anatomical differences were observed between the sexes. Females presented the typical two pairs of papillae (ureteral and genital) and males a single pair of urogenital papillae. The observed differences were confirmed when both pairs bred successfully in the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
0
0
Order By: Relevance
“…The existence of similar structures has been described in tegu lizards (Morici et al 2017;Spadola et al 2022), male Tiliqua sp. (Spadola et al 2021) and has been recently confirmed also in another monomorphic genus, the helodermatid lizards (our unpublished results).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The existence of similar structures has been described in tegu lizards (Morici et al 2017;Spadola et al 2022), male Tiliqua sp. (Spadola et al 2021) and has been recently confirmed also in another monomorphic genus, the helodermatid lizards (our unpublished results).…”
Section: Discussionsupporting
confidence: 78%
“…Recently, cloacal anatomy and sex identification with the use of cloacoscopy have been published for another monomorphic lizard, Tiliqua sp. (Spadola et al 2021).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation